Targeting RGD-binding integrins as an integrative therapy for diabetic retinopathy and neovascular age-related macular degeneration. (November 2021) - Van Hove, Inge; Hu, Tjing-Tjing; Beets, Karen; Van Bergen, Tine; Etienne, Isabelle; Stitt, Alan W.; Vermassen, Elke; Feyen, Jean H.M.
Abstract: Integrins are a class of transmembrane receptors that are involved in a wide range of biological functions. Dysregulation of integrins has been implicated in many pathological processes and consequently, they are attractive therapeutic targets. In the ophthalmology arena, there is extensive evidence suggesting that integrins play an important role in diabetic retinopathy (DR), age-related macular degeneration (AMD), glaucoma, dry eye disease and retinal vein occlusion. For example, there is extensive evidence that arginyl-glycyl-aspartic acid (Arg-Gly-Asp; RGD)-binding integrins are involved in key disease hallmarks of DR and neovascular AMD (nvAMD), specifically inflammation, vascular leakage, angiogenesis and fibrosis. Based on such evidence, drugs that engage integrin-linked pathways have received attention for their potential to block all these vision-threatening pathways. This review focuses on the pathophysiological role that RGD-binding integrins can have in complex multifactorial retinal disorders like DR, diabetic macular edema (DME) and nvAMD, which are leading causes of blindness in developed countries. Special emphasis will be given on how RGD-binding integrins can modulate the intricate molecular pathways and regulate the underlying pathological mechanisms. For instance, the interplay between integrins and key molecular players such as growth factors, cytokines and enzymes will be summarized. In addition, recent clinical advances linked to targeting RGD-binding integrins in the context of DME and nvAMD will be discussed alongside future potential for limiting progression of these diseases. Highlights: RGD integrins affect a multitude of disease-related proteins and molecular pathways. RGD integrins are key players in inflammation, leakage, angiogenesis and fibrosis. Clinical trials support RGD integrin inhibition as treatment for retinal diseases. RGD integrin antagonism offers a broad therapeutic alternative for retinal diseases.